Synergy effects of biochar and polyacrylamide on plants growth and soil erosion control - Lee, Sang Soo; Shah, Haleem S; Awad, Yasser M; Kumar, Sandeep; Ok, Yong Sik (Environmental earth sciences, 2015)
Soil organic carbon (SOC) is one of the most critical factors determining soil quality or fertility. Recent survey has reported the severe degradation of SOC by soil erosion in agricultural fields throughout the world. To maintain soil quality or productivity, biochar (BC) or anionic polyacrylamide (PAM) has been recently suggested; however, the combination effects of BC and PAM have not been reported to date. This study evaluated the effect of BC, PAM or their mixture (BC+PAM) on soil quality, plant growth, and runoff and soil loss under simulated and natural rainfalls. Applications of BC promoted growth of soybean (C₃ type) and maize (C₄ type) plants and maintained soil physical properties such as water retention and stability. Our findings showed that BC+PAM was the best for plant growth, even other subject amendments were not worse. Addition of BC may lead to accelerate the metabolic-performance capacity of plants, especially C₃ plant, due to sufficient C source. For runoff and soil loss tests, all amendments increased runoff compared to the control possibly due to clogging soil pore by viscous PAM solution application and decreased soil loss due to clay flocculation and aggregate stabilization by PAM, and water adsorbing capacity of BC. The use of BC+PAM can be a new, excellent strategy to promote plant growth and reduce soil loss; however, optimum application method should be considered carefully prior to its practical use.